A history of EU-ACP private sector development policies (1975-2000) - (:unkn) unknown (My University, 2018)
This thesis studies the historical construction of private sector development policies, so-calledpriority policies of development aid. The implementation of these policies is studied here in the context ofthe relations between the EU institutions and the countries of the Africa-Caribbean-Pacific (ACP) groupfrom 1975 to 2000, during the Lomé Conventions. Although these policies represent a dominant objectiveof development aid today, they already existed in other forms as early as 1975. The evolution of adevelopment aid public policy is studied with a particular focus on the institutions in Brussels. The research looks at the links of the services of the Directorate-General for Development (DG VIII) of the European Commission with the Community or joint instruments serving this policy: the European Investment Bank and the Centre for Industrial Development. The history of these policies is interspersed with evolutions that are specific to certain transnational economic networks, member states, and other international organizations (World Bank, OECD). The research is placed in a double perspective of international organizations history and a transnational history of economic networks, to trace the individual socioprofessional trajectories and the institutional dynamics that explain the making of European development policies. Three stages are studied: industrial co-operation (1975-1985); the emergence of “private sector development” as a new hegemonic terminology within the OECD's DAC (1985-1995); the time for institutional and operational reforms of development aid (1995-2000).
Keywords: African Research